Opportunities and challenges for deep brain stimulation electrode-guided neurofeedback for symptom mitigation in neurological and psychiatric disorders - Oliver Bichsel; Lukas Imbach; Roger Gassert (Journal of NeuroEngineering and Rehabilitation)
Abstract Neurological and psychiatric disorders are among the leading causes of disability worldwide. With our increasing understanding of brain circuit malfunctions leading to clinical manifestations, neuromodulation techniques intervening directly at the circuit level have gained popularity as a complement to pharmacological intervention. These approaches include deep brain stimulation (DBS) and, more recently, neurofeedback. Currently, neurofeedback mainly relies on non-invasive neuroimaging but is either confined to the experimental setting or only provides nebulous cortical feedback. Interestingly, some recent DBS systems can stream electrophysiological recordings, providing a unique opportunity for neurofeedback to self-regulate ongoing brain activity at deep brain targets. Herein, we review recent studies showing rapid learning of DBS electrode-guided neurofeedback in individuals with Parkinson’s disease, with some studies supporting improved motor outcome. We provide a perspective on further applications of DBS electrode-guided neurofeedback, which encompass a wide range of disorders currently investigated with neurofeedback, focusing on other movement disorders, epilepsy, stroke and pain. The successful translation of this novel therapy approach to clinical practice still depends on technological hurdles that need to be overcome as well as larger cohorts demonstrating a meaningful benefit. As an adjunct treatment, this technique could ultimately alleviate symptoms and reduce long-term dependence on medication and DBS.